Improving Students’ Cognitive Abilities through Jarimatics Method at Al-Hidayah Negarasaka Village Negerikaton District Pesawaran District - Ariyanto, Bambang; Misrodin, Misrodin (Bulletin of Pedagogical Research, 2024)
This research is based on the researcher's observations and experience, that cognitive abilities through Jarimatika are not just a medium for counting, but by using the Jarimatika method, children feel happy and there is no pressure. Using the Jarimatika method can train children's counting, and increase children's numeracy skills. Based on the background of the problem, the research problem was formulated, namely: whether the application of learning through the Jarimatika method is able to improve the numeracy skills of Group B RA students. Al-Hidayah, Negarasaka Village, Negerikaton District, Pesawaran Regency. This research uses a collaborative Classroom Action Research (CAR) approach. This research was carried out in two cycles, using instruments in the form of a calculation work sheet using the Jarimatika method and a teacher observation sheet. The improvement can be seen from the children's learning completeness in developing gross motor skills which has increased, this can be seen from the children's learning completeness in the Pras Cycle with a total of 40% completeness. then in cycle I it increased by 46.67%, and in cycle II the percentage of children's learning completion increased to 86.67%. Keywords: Jarimatics Method, Improving Students’ Cognitive, Numeracy Skills